Permanent and Transitory Responses to Capital Gains Taxes: Evidence from a Lifetime Exemption in Canada - Adam M. Lavecchia; Alisa Tazhitdinova (Institute of Labor Economics (IZA), 2021)
Using panel data on a 20% random sample of Canadian taxpayers, we study behavioral responses to the cancellation of a lifetime capital gains exemption that resulted in increased capital gains taxation for some individuals. The unique setting allows us to distinguish between short-term avoidance responses and permanent responses to capital gains taxes. We show that the exemption did not change the number of taxpayers reporting positive capital gains, and thus unlikely resulted in increased participation in capital markets. However, the exemption cancellation slightly increased capital gains realizations of the existing traders.
Keywords: H24; H31; G51; 330; capital gains tax; real responses; avoidance; re-timing